PENEGAKAN HUKUM TERHADAP ZONA LARANGAN TERBANG BAGI PESAWAT SIPIL ASING DI INDONESIA - Silmiwati Silmiwati (University Of Bengkulu Law Journal, 2017)
The sovereignty is the highest authority owned by the state. In the sovereignty decided contained matter relating with the power and responsibility for the state territory. The state have a responsibility to own territory and that state has the power to be competent for apply the no-fly zone. Indonesian state is the sovereign state, therefore with the implementation of no-fly zone meant that no reduction in the sovereignty of Indonesian state. The results showed that no-fly zone was regulated in International Law on Paris Convention 1919 Article 3 and 4, and Chicago Convention 1944 Article 9. The National Law, no-fly zone was regulated on Article 7 Legislation Number 1 of 2009 about Aviation. Indonesia has setting the rule of no-fly zone in the region WAP7 Surabaya Naval Base and WAP23 Balikpapan Flare. Indonesia Air Force has working to maintain the sovereignty of Indonesia.